ANALISIS YURIDIS KEWENANGAN NOTARIS YANG TETAP MENJALANKAN JABATAN SETELAH MELAKUKAN TINDAK PIDANA (STUDI KASUS ATAS PUTUSAN NOMOR 300/PID.B/2015/PN.DPS) - TYAN PUSPITA DEWI (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Budiman Ginting, SH, MHum2. Prof. Dr. Madiasa Abilizar, SH, MS3. Notaris Dr. Henry Sinaga, SH, MKn The position of a Notary as a public official is as one of state organ mandated with part of state duties and authorities such as the tasks, obligations, and authority to provide services to the society in civil affairs. Regarding his authority, a Notary can be held accountable for his actions in making authentic deeds which are not in accordance with the prevailing regulations or made illegally. Taking liability is the attitude of insuring all risks or consequences incurred by an action. Many notaries are involved in legal problems in the last decade, either the persons concerned is aware or not about it. One of the case, as an example, is the trust abuse in using the money deposited for paying the tax of a land sale and purchase by a client to the concerned Notary. The research problems are: 1)) how the authority of a Notary is, as a deed maker, pursuant to the prevailing laws and regulations; 2) How legal sanctions for the Notary who performs a criminal act of embezzlement are regulated and handed down; and 3) how the legal consideration is concerning the Case on Criminal Act of Embezzlement of money deposited for paying tax. Keywords : Authority, Notary, Criminal Act